2015
DOI: 10.1155/2015/314194
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Quality of Life in Severely Obese Adults during a Two-Year Lifestyle Intervention Programme

Abstract: It is unknown how changes in physical activity may affect changes in quality of life (QoL) outcomes during lifestyle interventions for severely obese adults. The purpose of this study was to examine associations in the patterns of change between objectively assessed physical activity as the independent variable and physical, mental, and obesity-specific QoL and life satisfaction as the dependent variables during a two-year lifestyle intervention. Forty-nine severely obese adults (37 women; 43.6 ± 9.4 years; bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 54 publications
0
15
1
2
Order By: Relevance
“…It can also be concluded that exercise has a positive effect on life satisfaction. In another study on obese adults, Jepsen et al (2015) concluded that physical activity in obese adults is also positively associated with quality of life. This study supports the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be concluded that exercise has a positive effect on life satisfaction. In another study on obese adults, Jepsen et al (2015) concluded that physical activity in obese adults is also positively associated with quality of life. This study supports the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we are unable to state with certainty whether weight loss caused improved quality of life. Other variables not assessed in this study could have played a role in quality of life improvements, such as physical activity (38,39) or type of diet (40,41). Furthermore, we cannot generalize these results beyond the clinical trial setting, as differences in quality of life have been observed in varying subgroups of persons with obesity (42,43).…”
Section: Clinical Obesitymentioning
confidence: 88%
“…이상에서 체중 감량이 삶의 질 개선에 미치는 영향을 연구한 28편의 연구를 살펴본 결과, 이 중에서 22편이 체 중 감량 후 삶의 질이 개선되었다고 보고하였다 10,11,13,14,17-20, 22-25,29,31-39) . 12,15,16,30,31) PCS 10,11,13,17,19,32,33,[35][36][37][38][39] , MCS…”
Section: Eq-5d를unclassified